Tailored for Combat: The Conservation of an Elizabethan Jack of Plate. (3rd July 2019) - Piper, Lauren
Abstract : The collection of the Royal Armouries contains just nine examples of a type of armoured doublet known as the jack of plate and yet this group still constitutes the largest known collection of such objects anywhere in the world. This paper describes the interventive conservation treatment of a late 16th century jack of plate. In its severely deteriorated state the garment was unfit for display or study and extensive work was required to make it stable and to facilitate its interpretation. The conservation approach adopted, including the creation of a bespoke mount, as well as the dyeing and application of appropriate support fabrics, is discussed.